Infants Exposure to Aflatoxin M1 from Mothers Breast Milk in Iran - AH Maghsood; SA Ghiasain (Tehran University of Medical Sciences, 2012)
Background: The occurrence of aflatoxin M1 (AFM1) in milk, especially breast milk, is a valuable biomarker for ex-posure determination to aflatoxin B1 (AFB1). In the present study, the risk of exposure to AFM1 in infants fed breast milk was investigated. Methods: An enzyme-linked immunosorbent assay (ELISA) was used for the analysis of AFM1 in breast milk samples from 132 lactating mothers referred to four urban Mothers and Babies Care Unit of Hamadan, western Iran. Results: AFM1 was detected in eight samples (6.06%) at mean concentration of 9.45 ng/L. The minimum and maxi-mum of concentration was 7.1 to 10.8 ng/L, respectively. Although the concentration of AFM1 in none of the samples was higher than the maximum tolerance limit accepted by USA and European Union (25 ng/kg) however, 25% had a level of AFM1 above the allowable level of Australia and Switzerland legal limit (10 ng/L). Conclusions: Lactating mothers and infants in western parts of Iran could be at risk for AFB1 and AFM1 exposure, respectively. Considering all this information, the investigation of AFM1 in lactating mothers as a biomarker for post-natal exposure of infants to this carcinogen deserves further studies in various seasons and different parts of Iran